FOMO at the Vineyard : A Microstudy of Wine Tourists’ Revisit Intentions Based on Digital Triggers - Ravichandran, Sabari Shankar (Indian Journal of Marketing, 2026)
Purpose : Wine tourism, which is a smaller and specific area of the tourism sector, is a developing market with numerous aspects of digital media and emotional connection. Tourist visits can be influenced by various social media related fears and concerns, such as the fear of missing out. This study investigated the role which FOMO, originating from internet social networking sites, played on the travel plans of tourists. Methodology : This study used a mixed methods approach, involving both quantitative and qualitative data. The quantitative data was obtained from a survey of 260 people. Using a qualitative analysis approach, the content of the users’ online posts was investigated. This study examined the emotional and digital cues that caused tourists from both domestic and international areas to plan another visit to a site. Findings : The study found that posting holiday photos and reviews on the internet could significantly influence the travelling behaviour of tourists. The feeling of missing out (FOMO) was triggered by visually engaging content, narratives from peers and influencers, and this resulted in perceived emotional voids. Among Indian travellers, it was discovered that Instagram Reels, reviews on TripAdvisor, and exclusive promotions focused on exclusivity received a high level of response from social validation. Implications : This research found that wine tourism businesses should adopt emotionally aware digital marketing strategies to promote repeat visits. Originality : This study made a contribution to the field of tourism marketing by identifying the effects of the fear of missing out on the travel decisions of tourists. The results showed how this psychological aspect influenced tourist intentions. The theoretical concept also had a cross disciplinary application in both digital marketing and branding of the destination in the development of wine tourism industry in India.